O consumidor brasileiro de marcas de luxo: uma descrição e segmentação psicográfica por valores - Cypriano, Isabel Maria Manini (2013)
The field of this dissertation is the Marketing applied to Luxury brands for clothes and accessories, a description and a segmentation of Brazilian Luxury customers, regarding the consumer psychographic traits. The Psychographics is used to market understanding and to deep evaluate the segments, going beyond demographics variables (Blackwell, Miniard, Engel, 2005). The Psychographics utilizes the subjective characteristics of customers such as lifestyle, personality, attitude, activities, interests , values (Tomanari, 2003). Here the psychographics traits are the consumer’s values. Values are human properties that hardly change; they are behavior influencers and are shared by individuals that belong to the same culture changing according to cultural specificities (Hemzo, Silva, 2009). The psychographics traits are less universal and more likely to make sense in a particular culture, (the Brazilian one, in this dissertation). Brazil, one of the BRICS (Brazil, Russia, China, India and South Africa) is a developing economy, with ascending social classes and a rising demand for luxury brands and goods. In Brazil, the consumption of luxury brands, from the 2000s, had several causes. Economic conditions and the insertion in the global market facilitated the purchase of imported goods. However, the phenomenon of luxury differs in its traditional markets (France and Italy). This leads to the conclusion that, in emerging markets, luxury undergoes further definitions and symbols, sometimes differing from those of the countries of origin of brands. Therefore, one based on psychographic traits consumer segmentation may help the management of these brands in Brazil, which this dissertation addresses.